Monetary Policy vs. Fiscal Policy: Which Is More Influential Against Inflation in Indonesia? (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2022)
This study aims to determine and analyze which one is more influential or has the highest contribution to inflation, by comparing the variables of interest rates and government spending. This type of research is descriptive research, where the data used is secondary data in the form of time series data from 1991 to 2021 obtained from related institutions and institutions, which are analyzed using the Vector Error Correction Model (VECM) method. Stages of Stationarity Test, Cointegration Test, Impulse Response Function (IRF), and Variance Decomposition (VDC). The findings of this study are the overall variability of inflation in both the short and long term from interest rates of 79.95% in the short term and 71.44% in the long term. Meanwhile, the variability of government spending is 0.03% in the short term and 4.69% in the long term. So it can be concluded from the interest rate variable and government spending, it is interest rates that most influence inflation in Indonesia.